2016
DOI: 10.1111/nph.14068
|View full text |Cite
|
Sign up to set email alerts
|

Scale dependence of canopy trait distributions along a tropical forest elevation gradient

Abstract: Average responses of forest foliar traits to elevation are well understood, but far less is known about trait distributional responses to elevation at multiple ecological scales. This limits our understanding of the ecological scales at which trait variation occurs in response to environmental drivers and change. We analyzed and compared multiple canopy foliar trait distributions using field sampling and airborne imaging spectroscopy along an Andes-to-Amazon elevation gradient. Field-estimated traits were gene… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

9
87
1
5

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 68 publications
(102 citation statements)
references
References 69 publications
9
87
1
5
Order By: Relevance
“…We added the limited amount of studies where community-weighted means were reported along one "single mountain range system", hence neglecting a recent and relevant contribution from Asner and Martin (2016). Our comparison showed that the decreasing trend in LNC was consistent with the other studies from South America (Asner et al, 2016b;Van de Weg et al, 2009), but not with Southeast Asia, where no significant trend was found (Kitayama and Aiba, 2002). However, leaf mass area (LMA; the inverse of SLA) of all studies showed a similar, increasing trend with elevation.…”
Section: Discussionsupporting
confidence: 88%
See 2 more Smart Citations
“…We added the limited amount of studies where community-weighted means were reported along one "single mountain range system", hence neglecting a recent and relevant contribution from Asner and Martin (2016). Our comparison showed that the decreasing trend in LNC was consistent with the other studies from South America (Asner et al, 2016b;Van de Weg et al, 2009), but not with Southeast Asia, where no significant trend was found (Kitayama and Aiba, 2002). However, leaf mass area (LMA; the inverse of SLA) of all studies showed a similar, increasing trend with elevation.…”
Section: Discussionsupporting
confidence: 88%
“…Subsequently, to calculate community-level traits and leaf δ 15 N per plot, we calculated a basal area weighted-average canopy value and standard deviation using the species composition and the species averages, following Asner et al (2016b). Hence,…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…This provides an opportunity to understand how the carbon dynamics of tropical forests vary with elevation, as well as to apply the process‐based framework described earlier to generate a quantitative comparison of the relative importance of various factors influencing growth rates and biomass among forests along this elevation transect. These sites are also the location of the CHAMBASA project (Y. Malhi et al ., unpublished), which explores the relationships between plant traits and ecosystem function; hence this study presents and explains the benchmark productivity data for various CHAMBASA companion papers (Asner et al ., ; Bahar et al ., ; Chavana‐Bryant et al ., ; Goldsmith et al ., ). It also provides a consistent dataset suitable for testing and aiding ecosystem model development.…”
Section: Introductionmentioning
confidence: 98%
“…Full-range imaging spectroscopy utilizes contiguous, high-spectral-resolution measurements of reflected solar radiation in the 350-2510 nm wavelength region to estimate canopy traits such as water, nutrient, and defense compounds [3][4][5]. Although imaging spectroscopy has evolved in step with technological, computing, and modeling advances [6,7], few studies have attempted the retrieval of multiple foliar traits needed to characterize functional diversity.…”
Section: Introductionmentioning
confidence: 99%